PELUANG DAN TANTANGAN DALAM KARIR GENERASI Z DI ERA REVOLUSI INDUSTRI 5.0 - Riris Debora Tamba (Jurnal Komunikasi, 2025)
Industrial Revolution 5.0 brings significant changes to society and the world economy. This era, which is called the era of automation and digitalization, is a collaboration between technology and humans. Therefore, Generation Z is required to be able to adapt with rapid and dynamic changes. This research aims to determine the opportunities and challenges faced by Generation Z in their careers in the era of industrial revolution 5.0. This research method uses a literature study approach that studies reference books, journal articles, and topics related to the topic. The data collection technique uses a literature study approach. The research results show that the Industrial Revolution 5.0 which uses the presence of intellectual intelligence (AI), Internet of Things (IoT), provides convenience and efficiency for generation z in their careers and indirectly opens up opportunities to compete in the global world. However, this opportunity has challenges that must be faced. For this reason, a government strategy and an active role for Generation Z are needed in facing these challenges.